Revitalization of History Learning in Senior High Schools - La Ode Hasirun; Muhammad Aqil; Megiridha Loppies (JURNAL PENDIDIKAN IPS, 2025)
The objectives of this study are as follows: (1) to identify the history learning process at Senior High Schools; (2) to examine the factors contributing to the lack of student interest in history subjects at the senior high school level; (3) to explore efforts to increase students’ interest in learning history. The research method used is qualitative with a library research approach. Data sources were obtained through observations and interviews conducted with teachers and students. The data analysis techniques applied include data reduction, interpretation, and conclusion drawing. The results of the study show that: (1) The history learning process in Senior High Schools is generally still conventional, dominated by lecture methods and written assignments. This leads to low student engagement in the learning process, which negatively affects their interest and understanding of historical material; (2) The limited use of visual media, documentary videos, or digital technology in history learning makes the material feel dry and difficult to understand, especially for students with visual and kinesthetic learning styles; (3) The implementation of varied, interactive, contextual learning methods combined with digital-era technology integration can help increase students’ interest in learning history.